Amino acid sequence of rabbit kidney neutral endopeptidase 24.11 (enkephalinase) deduced from a complementary DNA. - Devault, A (1987)
Neutral endopeptidase (EC 3.4.24.11) is a major constituent of kidney brush border membranes. It is also present in the brain where it has been shown to be involved in the inactivation of opioid peptides, methionine- and leucine-enkephalins. For this reason this enzyme is often called 'enkephalinase'. In order to characterize the primary structure of the enzyme, oligonucleotide probes were designed from partial amino acid sequences and used to isolate clones from kidney cDNA libraries. Sequencing of the cDNA inserts revealed the complete primary structure of the enzyme. Neutral endopeptidase consists of 750 amino acids. It contains a short N-terminal cytoplasmic domain (27 amino acids), a single membrane-spanning segment (23 amino acids) and an extracellular domain that comprises most of the protein mass. The comparison of the primary structure of neutral endopeptidase with that of thermolysin, a bacterial Zn-metallopeptidase, indicates that most of the amino acid residues involved in Zn coordination and catalytic activity in thermolysin are found within highly honmologous sequences in neutral endopeptidase.